An Analysis of An English Textbook “English in Mind Second Edition - Students’ Book 3” for The Tenth Grade of The Vocational High School Based on Ur’s Criteria - Gita Anggreyni; Kiagus Baluqiah (Teaching English and Language Learning English Journal, 2022)
Abstract This research had an objective to find out whether the English textbook of technical vocational high school is suitable for Ur’s criteria. The method used in this research was a descriptive quantitative method. The object in this research was an English book at the Vocational High School (SMK) entitled English in Mind Second Edition – Student’s book 3. The data were analyzed by the instrument of this research namely a table checklist consisting of a good criteria of English textbook by Ur (1996). The findings showed that the textbook met the criteria by Ur (1996) with a score of 55. It means that this textbook has level of a fair textbook, so this textbook could be used for technical vocational high school. This textbook fulfilled 11 criteria of 20 criteria by Ur (1996). Meanwhile, 9 criteria were unavailable in the textbook. Therefore, it is a challenge for the teacher in using the textbook for English teaching and learning. The teacher should complete the unavailable criteria of textbook by adding the materials or media from others. Finally, the researcher suggests that this research can be references to find detailed information about this textbook by using other theories of textbook assessment. Keywords: English Textbook, Suitability, Ur’s criteria.